Sociotechnical adequacy for agroecology and agrourbania - Canavesi, Flaviane de Carvalho (2023)
This chapter presents principles of the scientific field of Agroecology that dialogue withthe approachof Science,Technology and Society (CTS).It is important tovalue popular sociotechnical subjects,menand women,since the constructionof knowledge is collective and involves various forms of knowledge and dialogues,whichmay be academic and non-academic.The objective of this chapter is topresent agroecological experiences developed frompraxis,having as relevance the sociotechnical adequacy inwhichknowledge and productionof goods and services are contextualized tothe reality and interests of those involved.The way suchexperiences are presented reflect,at first,the theoretical understanding of studies conducted inthe course Fundamentals inScience,Technology and Society - CTS Habitat,Agroecology,Solidarity Economy and EcosystemHealth,followed by reports that seek toreflect the learning fromthe experiences presented.It is anexercise of analysis and learning of the way inwhichthe CTS approachcanbe turned into visible in the construction of agroecological knowledge.